2019
DOI: 10.1016/s1473-3099(18)30568-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two schedules of two-dose priming with the ten-valent pneumococcal conjugate vaccine in Nepalese children: an open-label, randomised non-inferiority controlled trial

Abstract: Background: Nepalese infants receive PCV10 with a one-month interval between priming doses for programmatic reasons. We aimed to investigate whether immune responses to PCV10 serotypes were non-inferior if the second priming dose of PCV10 was delivered at a one-month as opposed to a two-month interval. Methods: We conducted an open-label, randomised, parallel group trial in healthy Nepalese infants aged 40-60 days in Kathmandu, Nepal. Participants were randomised (1:1) using a computer-generated list with rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 11 , 12 Another trial from Nepal found that a 2-month interval between doses in a primary series resulted in a higher antibody response than a 1-month interval. 13 Therefore, timing of doses during the primary vaccination series is an important consideration because maximising protection against invasive pneumococcal disease in the intervening period until the booster dose is crucial.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Another trial from Nepal found that a 2-month interval between doses in a primary series resulted in a higher antibody response than a 1-month interval. 13 Therefore, timing of doses during the primary vaccination series is an important consideration because maximising protection against invasive pneumococcal disease in the intervening period until the booster dose is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a cross-sectional follow-up study at Patan Hospital among participants of our previous trial comparing different 2-dose priming schedules (6 + 10 weeks vs. 6 + 14 weeks) for PCV10. 14 Oxford Tropical Research Ethics Committee (OxTREC Ref no: 34-17) and Nepal Health Research Council (NHRC Reg no: 459/2017) approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a cross-sectional follow-up study at Patan Hospital among participants of our previous trial comparing different 2-dose priming schedules (6 + 10 weeks vs. 6 + 14 weeks) for PCV10. 14 We approached by telephone, 287 participants who completed the original study, and explained the details of the study to them. We invited interested participants to visit the Paediatric Research Unit at Patan Hospital, where we provided them with an information sheet and discussed the study in more detail.…”
Section: Study Design and Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations